DEFINITION OF NATIONAL RESILIENCE IN UKRAINE IN THE SCIENTIFIC OPINION OF DOMESTIC RESEARCHERS (PART 1) - L. Korolchuk, Olena; M. Bilynska, Maryna; Y. Mokretsov, Sergii; A. Gaievska, Larysa; A. Kulhinskyi, Yevhenii (Revista Gênero e Interdisciplinaridade, 2021)
The urgency and importance of this issue are due to the fact that the government, public administration, civil society are increasingly emphasizing the need to update strategies to ensure stability, resilience of the nation and the country to modern risks and disasters that have become complex, hybrid, less predictable. The purpose of this article is to highlight the issues of formation and development of national resilience in modern scientific thought in Ukraine and the search for a relevant definition of this concept. The leading approach to the study of this issue was inductive thematic analysis, which revealed the achievements of domestic science, identified major trends in the views of experts on the problem, explored the relevance and level of knowledge of the problem of determining national resilience in Ukraine. The article reveals that today there is still no generalized, agreed definition of national resilience in Ukraine; the relevance of this issue in the light of the impact of modern risks and threats is disclosed; the main publications on this topic are found to address issues of national stability and security in various spheres of state life: public administration, socio-humanitarian, financial and economic, national security, civil society development, etc. and an author's definition of national resilience of Ukraine is provided. The materials of the article have practical value for the development and implementation of a strategy for the development of national resilience in Ukraine in order to prevent and overcome today's complex risks and threats and provide a fruitful environment for the well-being of descendants. Also, it can be used by scientists, practitioners, government institutions and public administration bodies, representatives of civil society for the development and implementation of this concept in Ukraine.